EFFECT OF ANISOTROPY AND SPATIAL COMPOUND IMAGING ON RENAL CORTICAL ECHOGENICITY IN DOGS. Issue 6 (13th June 2013) - Ruth, Jeffrey D.; Heng, Hock Gan; Miller, Margaret A.; Constable, Peter D.
Abstract : The echogenicity of the renal cortex is an important parameter to consider in dogs that are suspected to have renal dysfunction. Focal increases in echogenicity have been attributed to neoplasia, infection, calcification, fibrosis, gas, and infarction. Anisotropic backscatter has been described as a source of focally increased renal cortical echogenicity in several species. The source of anisotropy appears to be the medullary rays, which are oriented perpendicular to the renal capsule. Spatial compound imaging (SCI) is an ultrasound setting that uses beam steering to acquire and average several overlapping scans of an object from different view angles, creating a compound image that is updated in real time. The impact of insonation angle and SCI on renal cortical echogenicity was evaluated ex vivo in eight kidneys from four dogs. Significant angle‐dependent differences in cortical echogenicity were detected with both microconvex and linear transducers ( P < 0.0001). Furthermore, the angle‐dependent echogenicity differences persisted when SCI mode was used. Our finding that echogenicity was increased using a perpendicular insonation angle (90°) relative to the tubules, compared to a parallel insonation angle (0°) should assist in the interpretation of ultrasonographic images of the dog kidney.